2001
DOI: 10.1017/s0140525x01003910
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of embodiment: A field theory of infant perseverative reaching

Abstract: The overall goal of this target article is to demonstrate a mechanism for an embodied cognition. The particular vehicle is a much-studied, but still widely debated phenomenon seen in 7–12 month-old-infants. In Piaget's classic “A-not-B error,” infants who have successfully uncovered a toy at location “A” continue to reach to that location even after they watch the toy hidden in a nearby location “B.” Here, we question the traditional explanations of the error as an indicator of infants' concepts of objects or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
675
1
16

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 898 publications
(722 citation statements)
references
References 325 publications
(336 reference statements)
30
675
1
16
Order By: Relevance
“…This model accounts for infants' performance in a manner comparable to the account proposed by Thelen et al (2001) and the simulations reported here. For instance, developmental change in the PDP model is achieved through strengthening connections within the hidden layer, which effectively produces a more robust "active" memory for the current trial.…”
Section: Comparing the Dft To Other Modelssupporting
confidence: 69%
See 1 more Smart Citation
“…This model accounts for infants' performance in a manner comparable to the account proposed by Thelen et al (2001) and the simulations reported here. For instance, developmental change in the PDP model is achieved through strengthening connections within the hidden layer, which effectively produces a more robust "active" memory for the current trial.…”
Section: Comparing the Dft To Other Modelssupporting
confidence: 69%
“…The dynamic field framework was originally developed to capture the dynamics of neural activation in visual cortex (Amari, 1977). More recently, this framework has been extended to account for the processes that underlie saccadic eye movements (Kopecz & Schöner, 1995;Wilimzig, Schneider & Schöner, 2006), motor planning (Erlhagen & Schöner, 2002;Schutte & Spencer, 2007b), infants' performance in Piaget's Anot-B task (Thelen, Schöner, Scheier & Smith, 2001), the dynamics of neural activation in motor and premotor cortex (Bastian, Riehle, Erlhagen & Schöner, 1998;Bastian, Schöner & Riehle, 2003), and the behavior of autonomous robots (Bicho, Mallet & Schöner, 2000;Iossifidis & Schöner, 2006;Steinhage & Schöner, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a narrow focus on cognition combined with a dismissal of the role of embodiment for this very cognition is at odds with recent research in cognitive neuroscience, developmental psychology and phenomenological strands of philosophy (see Gallagher, 2005;Thelen, 2001;Clarke, 1997;Damasio, 1994;Varela, Thompson and Rosch, 1991). Despite the differences between these strands of research, they all examine how cognition is necessarily embodied: the individual's unique sensory-motor capabilities enable her or him to interact with others, and cognition "arises from bodily interactions with the world" and "depends on the kinds of experiences that come from having a body with particular perceptual and motor capacities that are inseparably linked and that together form the matrix within which reasoning, memory, emotion, language and all other aspects of mental life are meshed" (Thelen et al, 2001, 1).…”
Section: Why These Conceptions Are Not Enoughmentioning
confidence: 99%
“…The DNF approach has successfully been employed in models of motor planning for both eye movements (Kopecz and Schöner 1995;Trappenberg et al 2001) and reach movements (Erlhagen and Schöner 2002;Cisek 2006). On a more abstract level, the approach is used in behavioral models of spatial cognition, visual working memory, and development (Thelen et al 2001;Simmering et al 2008;Johnson et al 2008). …”
Section: Dynamic Neural Fieldsmentioning
confidence: 99%